Convenient preparations of racemic and enantiopure methyl 6-oxopipecolate - Davies, C; Heightman, T; Hermitage, SA; Moloney, M (1996)
Short, convenient syntheses of racemic and enantiopure methyl 6-oxopipecolate are described, starting from either pipecolic acid or (S)-lysine respectively. The sequence for the latter compound relies upon improved methodology for the oxidation of C-6 of lysine.